A method of determining the carbon emission reduction contribution of regional distribution networks based on spherical fuzzy sets - Du, Puliang; Yang, Miaoheng; Hu, Wei; Wang, Pengfei; Xing, Qiang (Frontiers in Energy Research, 2024)
Introduction An innovative methodology is proposed to delve into the pivotal role of regional distribution networks (RDNs) in fostering low-carbon development. Methods The methodology first constructs an evaluation framework encompassing various dimensions and then integrates spherical fuzzy sets (SFSs) with the best-worst method (BWM), enabling the precise calculation of indicator weight parameters. Subsequently, we employ the measurement of alternatives and ranking according to compromise solution (MARCOS) with SFSs to process and synthesize decision making information. Results Take the Shanghai region as an example, results show that C4 has the highest performance and C10 has the lowest. Discussion In conclusion, this research presents a significant step forward in understanding the importance of RDNs in promoting low-carbon development and offers a practical approach for decision-makers to assess and enhance the performance of RDNs.